GAMBARAN KREATIVITAS GURU DALAM PENERAPAN KURIKULUM 2013 SEKOLAH DASAR DI SURABAYA - Uni Kartika Sari; Nono Hery Yoenanto (UIN Sunan Kalijaga, 2019)
This research aims to determine teacher creativity in the 2013 curriculum implementation of elementary school in Surabaya. The teacher's creativity refers to Guilford's creativity (1967) that involves fluency of thinking, flexibility, originality and elaboration. Meanwhile, the Bronfenbrenner’s ecological system theory used as the grand theory. This research focuses on “X” and “Y” elementary schools. The instrumental case study took as design research, which used variant participants who interviewed by researcher such as teachers, principals and parents. This study uses a thematic analysis of data. Findings indicate that teacher creativity in the 2013 curriculum implementation have been carried out well where from fluency, flexibility and elaboration in planning of learning, process and evaluating learning outcomes of student. Meanwhile, the originality that related with the teacher's idea in planning learning still lacks authenticity. Furthermore, teacher also lack to creativity of assessment due to the thematic assessment content that depend respective educational units.